Current and Future Concepts in Treatment of Childhood Atopic Dermatitis Review - Elif Karakoç Aydıner; Safa Barış; Cevdet Özdemir (Güncel Pediatri)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder caused by a dysregulation of immune response to allergenic or non-allergenic stimuli. Interplay of several effector cells including migrating lymphocytes, fibrocytes, Langerhans cells, mast cells and epidermal keratinocytes enroll in the development of AD. Atopic dermatitis affects approximately 20% of children and persists in 6% of adults. Relieving acute exacerbations, improving the quality of life and prevention of side effects in the long term are the main steps of the management of AD. Mild to moderate cases can be controlled with avoidance of triggering factors, skin care and topical medications. In severe cases immune suppression is an option with cumulative toxicity and variable efficacy of drugs as a limiting factor. It is essential to develop safer and efficacious alternatives for the treatment of AD, especially in pediatric age group. (Journal of Current Pediatrics 2011; 9: 39-43)